Financial consumer protection principles in accordance with the Quran and Sunnah / Nur I’ffah Muhammad Nasir and Rusni Hassan. - Muhammad Nasir, Nur I’ffah; Hassan, Rusni (Universiti Teknologi Mara Selangor, 2019)
Consumer plays an essential role in the economy of a nation. In a competitive economy where the businesses and manufacturers may use exploitative means and unfair trade practices, there is an urgent need to protect the consumers against such malpractices. Financial consumers are of no exception. Reliable consumer protection helps to build consumer trust in financial institutions which subsequently contribute to the stability of the financial market. The Western scholars establish the existing standards and good practices on financial consumer protection based on ethics, however, it is also essential to develop Shariah standards and good practices for the Islamic finance industry because the different elements that exist between the Islamic and conventional finance industry. The purpose of this paper is to study the financial consumer protection mechanism from the Shariah sources of Quran and Sunnah. This paper is conceptual, mainly applying the content analysis approach that explores the works of Islamic scholars related to the concept of consumer protection.